Detection of Phage’s Lytic Activity Against Carbapenemase-Producing Klebsiella pneumoniae Isolates Using a High-Throughput Microbroth Growth Inhibition Assay - Paschalis Paranos; Spyros Pournaras; Joseph Meletiadis (Infectious Diseases and Therapy)
Abstract Introduction The host range of phages is usually assessed with the agar overlay method. However, this method is both cumbersome and subjective. Therefore, a microbroth assay was developed to assess host range and lytic activity patterns of phages in the agar overlay method against a collection of carbapenemase-producing Klebsiella pneumoniae (CRKP) isolates. Methods The host range of 11 K. pneumoniae-specific phages against 8 non-repetitive well-characterized CRKP isolates was assessed with the agar overlay method and a microbroth assay by monitoring optical density (OD) at 630 nm for 24 h at different phage concentrations (5 × 109–5 × 103 PFU/ml) and two bacterial inocula (5 × 106 and 5 × 108 CFU/ml). The lytic activity of phage–bacteria pairs with transparent/semi-transparent (N = 7), turbid (N = 6), and no (N = 6) lysis in overlay agar method was compared statistically with the growth inhibition at 6 and 24 h in the microbroth assay with analysis of variance (ANOVA), receiver operating characteristic curves (ROC) curves and Fisher’s exact test. Optimal cutoffs were determined, and sensitivity and specificity were calculated. Results Statistically significant differences of growth inhibition at 6 and 24 h for phage concentrations ≥ 5 × 108 PFU/ml for both inocula were found between phages with transparent/semi-transparent, turbid, and no lysis. ROC curve analysis indicated an optimal growth inhibition cutoff of ≥ 31% at high phage and bacteria concentrations for detecting phages with lysis and ≥ 61% at high-phage and low-bacteria concentrations for detecting phages with transparent/semi-transparent lysis with sensitivity/specificity 100%/100% and 100%/86%, respectively. Conclusions The microbroth growth inhibition assay provided fast, reliable, and objective results for K. pneumoniae phage host-range lytic activity differentiating different patterns of lysis in a high-throughput format.